Do MOOCs encourage corporate social responsibility or are they simply a marketing opportunity?. (November 2018) - Wakefield, Ann; Cartney, Pat; Christie, Janice; Smyth, Rebecca; Cooke, Alison; Jones, Tracey; King, Erin; White, Helen; Kennedy, Jennifer
Abstract: This paper explores institutional drivers for developing MOOCs by juxtaposing them against the original drivers for generating MOOCs: to offer open access education. However, the original impetus for MOOC development may be shifting towards a business oriented model. Therefore, instead of contributing to corporate social responsibility and inclusivity agendas facilitating open access to education, MOOCs are akin to an institution's shop window allowing the pseudo 'purchaser' the opportunity to glimpse behind the scenes. Hence, we ask: are MOOCs merely a sophisticated form of window dressing, showing pseudo 'purchasers' what institutions want them to see enticing them to purchase more lucrative products? Notwithstanding the motivation for developing MOOCs participants must first access them. Therefore the paper examines what MOOCs actually offer participants who are likely to access them and concludes by examining how MOOCs can be developed to facilitate better completion rates and encourage wider participation from hard to access groups.